Identification of Learning Theories in Learning Videos: A Case Study of Prospective Chemistry Teacher Students - Ruslan, Zuhrah Adminira; Munawwarah (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study investigates the ability of prospective chemistry teachers to identify learning theories embedded in instructional videos. A descriptive qualitative case study was conducted involving 48 students enrolled in the Foundations of Science Education course at Universitas Negeri Makassar. Three chemistry instructional videos were deliberately designed to incorporate elements of behaviorist, cognitivist, constructivist, humanistic, and cybernetic theories. Students analyzed the videos using an identification sheet to document their observations. The findings reveal varying levels of recognition across the learning theories. Constructivist theory was most frequently identified in Video 1, while behaviorist principles dominated Videos 2 and 3, particularly in segments emphasizing drill, repetition, and stimulus–response reinforcement. Cognitivist theory appeared consistently, though less prominently, across all videos. In contrast, humanistic and cybernetic perspectives were recognized to a lesser extent, suggesting that affective, motivational, and systemic components were less explicitly represented. These results underscore the importance of integrating diverse learning theories in video-based instruction to promote not only conceptual understanding but also motivation, empathy, and systemic thinking. The novelty of this research lies in positioning instructional videos as pedagogical representations that reveal prospective teachers’ reasoning about learning theories, rather than merely treating them as delivery tools. This approach provides a new lens for evaluating theoretical literacy in teacher education and emphasizes the need for reflective engagement with instructional media during teacher preparation.